Employer branding as a form of sport event sponsorship : the case of a multinational industrial firm - Paakkonen, Lasse (2017)
The growth of new industry sectors and the ascent of burgeoning economies have increased competition between companies to secure a skilled workforce. To ensure competitiveness in these rapidly changing markets, companies have striven to build successful branding strategies. Although employer branding is becoming a popular trend in the world of practicing managers and scholars, perspectives are still evolving. The purpose of this study was to examine the effectiveness of employer branding from the perspective of a business-to-business (B2B) multinational company´s (thereafter, “the case company”) current employees. In this study, a sport sponsorship project acted as an employer branding activity, which aimed to affect employee opinions toward the case company as an employer. The chosen research strategy was a single-case study, which was implemented by an electronic survey. The research target group included the case company´s current employees, and the questionnaire was sent to 3,200 individuals by e-mail. Overall, 716 employees participated in the survey, resulting in a response rate of 22.4%. The data were analyzed via SPPS statistics and PLS 3.2 software. The results of this study indicated that a sport sponsorship project, when used as an employer branding activity, had a positive impact on employee opinions toward the case company as an employer on multiple levels. The proposed hypotheses that were formed from previous literature were accepted, and strong support for the developed research model was obtained. This study is amongst the first to provide empirical results of employer branding in the sport sponsorship context. The positive outcomes underline the feasibility of sport sponsorship as an effective strategy for achieving employer branding goals.